2023
DOI: 10.1002/slct.202204132
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Functional Polyurethane Chemistry: From Structural Design to Applications

Abstract: Polyurethane has attracted the great attention of scientists because of its lightweight, high toughness, good wear resistance and corrosion resistance. In the past, polyurethane was mainly used in low‐end products because of its single function. With the development of science and technology, ordinary polyurethane has been unable to meet the diverse needs of people. In recent years, scientists have developed a lot of functional polyurethane: self‐healing polyurethane, antifouling polyurethane, antibacterial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 118 publications
(149 reference statements)
0
14
0
Order By: Relevance
“…The crude reaction mixture for PU1 (depolymerized in a separate experiment using toluene to avoid NMR spectrum peak overlap with THF) was analyzed by 1 H and 13 C NMR spectroscopy (Figures S3 and S4). Purified MDI and TDI samples also were analyzed by 1 H NMR spectroscopy as shown in Figure S5 (MDI samples: PU1, PU2, CPU1) and Figure S6 (TDI sample: CPU2) with spectra for pure standards shown for reference. The isolated MDI yields (i.e., the gravimetric yields of pure isocyanates recovered after separation from the reaction product mixtures) for PU1 and PU2 were ∼23% and ∼20% of the theoretical maximum values, respectively (Table 2).…”
Section: Pu Depolymerizationmentioning
confidence: 99%
“…The crude reaction mixture for PU1 (depolymerized in a separate experiment using toluene to avoid NMR spectrum peak overlap with THF) was analyzed by 1 H and 13 C NMR spectroscopy (Figures S3 and S4). Purified MDI and TDI samples also were analyzed by 1 H NMR spectroscopy as shown in Figure S5 (MDI samples: PU1, PU2, CPU1) and Figure S6 (TDI sample: CPU2) with spectra for pure standards shown for reference. The isolated MDI yields (i.e., the gravimetric yields of pure isocyanates recovered after separation from the reaction product mixtures) for PU1 and PU2 were ∼23% and ∼20% of the theoretical maximum values, respectively (Table 2).…”
Section: Pu Depolymerizationmentioning
confidence: 99%
“…Polyurethane (PU) is formed by the exothermic reaction of addition polymerization of isocyanate and polyol. 1 As a kind of polymer material, it is well suited to the concept of "designing materials based on performance requirements" in modern society, and makes full use of the advantages of highly adjustable composition, structure and overall performance. 2 Specifically, the main chain of PU consists of two parts: the soft segment is mainly composed of macromolecules such as polyol or polyamine, which provides flexibility and elasticity; the hard segment is mainly composed of diisocyanate and small molecule chain extenders, which have high rigidity and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane (PU) is formed by the exothermic reaction of addition polymerization of isocyanate and polyol 1 . As a kind of polymer material, it is well suited to the concept of “designing materials based on performance requirements” in modern society, and makes full use of the advantages of highly adjustable composition, structure and overall performance 2 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, recent research has shown that PU elastomers can be designed to exhibit shape memory behavior, electrical conductivity, or dielectric properties, thus presenting an even greater range of potential applications. 4 Currently, polyol raw materials for producing PUs are largely dependent on petroleum resources. Due to the gradual shortage of fossil fuel resources and the increasing awareness of environmental impact and resource conservation, using sustainable biomass polyols to prepare PU materials has become a hot research field.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, PU elastomers have a combination of excellent mechanical, physical, and chemical properties along with exceptional biocompatibility. , Therefore, these elastomeric systems are used in a diverse range of indoor, outdoor, underwater, and biomedical applications . Moreover, recent research has shown that PU elastomers can be designed to exhibit shape memory behavior, electrical conductivity, or dielectric properties, thus presenting an even greater range of potential applications …”
Section: Introductionmentioning
confidence: 99%